THE ROLE OF ORGANIZATIONAL CULTURE IN FORMING THE IMAGE AND IMPLEMENTING THE INNOVATION STRATEGY OF AN ENTERPRISE - POMAZ, Oleksandr; CHUIKO, Valeriia; IOFFE, Yelyzaveta; CHUI, Klavdiia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article systematically investigates the multifaceted role of organizational culture in the modern enterprise, focusing on its crucial impact on forming an appealing image and successfully implementing an innovation strategy. It acknowledges that in an environment of escalating competition and dynamic external changes, a company's operational effectiveness largely depends not only on its resource potential but also on the internal values, norms, and beliefs that shape its unique culture.A thorough analysis is conducted on the interconnection between organizational culture elements (such as openness to change, collaboration orientation, risk tolerance, and customer-centricity) and their influence on two key areas. First, it examines how these cultural factors contribute to creating a favorable innovation climate that encourages the generation of new ideas, experimentation, and their subsequent implementation. Emphasis is placed on the importance of psychological safety, fostering initiative, and cultivating knowledge exchange to stimulate innovative activity. Second, the study explores how organizational culture is projected externally, shaping a positive enterprise image among consumers, partners, investors, and potential employees. It highlights that an authentic image is a reflection of the internal culture, which demonstrates the company's values and ethical principles.Particular attention is given to the main mechanisms through which organizational culture acts as a strategic factor actively building competitive advantages. These mechanisms include leadership support for innovative behavior, fostering an atmosphere of trust and mutual respect, encouraging a willingness to take risks and learn from mistakes, and focusing on continuous improvement and customer orientation. The research findings confirm that purposeful management of organizational culture is a necessary condition for ensuring sustainable innovative development and strengthening the enterprise's reputation in the contemporary market.
Keywords: image; innovative strategy; enterprises; competitive advantage; organizational culture